New Prehospital Triage for Stroke Patients Significantly Reduces Transport Time of EVT Patients Without Delaying IVT - Cabal, Martin; Machova, Linda; Vaclavik, Daniel; Jasso, Petr; Holes, David; Volny, Ondrej; Bar, Michal (Frontiers in Neurology, 2021)
BACKGROUND AND PURPOSE—Ischemic stroke is a leading cause of mortality and morbidity worldwide. The time from stroke onset to treatment impacts clinical outcome. Here we examined whether changing a triage model from “drip and ship” to “mothership” yielded significant reductions of onset-to-groin time (OGT) in patients receiving EVT, and onset-to-needle time (ONT) in IVT-treated patients, compared to before FAST-PLUS test implementation. We also investigated whether the new triage improved clinical outcomes. METHODS—In a before/after multicenter study, we evaluated the effects of changing the prehospital triage system for suspected stroke patients in the Moravian–Silesian region, Czech Republic. In the new system, the validated FAST PLUS test is used to differentiate patients with suspected large vessel occlusion, and triage-positive patients are transported directly to the CSC. Time metrics and patient data were obtained from the regional EMS database and SITS database. RESULTS—For EVT patients, the median OGT was 213 min in 2015, and 142 min in 2018; and median TT was 142 min in 2015, and 47 min in 2018. For tPA patients, the median ONT was 110 min in 2015, and 109 min in 2018; and median TT was 41 min in 2015, and 48 min in 2018. Clinical outcome did not significantly change. The percentages of patients with favorable clinical outcome (mRS 0–2) were comparable between 2015 and 2018: 60% vs 59% in tPA patients, and 40% vs 44% in EVT patients. CONCLUSIONS—The new prehospital triage has yielded shorter onset-to-groin times for EVT patients. No changes were found in the onset-to-needle time for IVT-treated patients, or in the clinical outcome at 3 months after stroke onset.